Reproduction and the Constitution in the United States - Ziegler, Mary, 1982- author.
1 online resource (192 pages).
Keywords: Reproduction and the Constitution in the United States dissects the forces that shape US conflicts over birth control and abortion. In 1973, the United States Supreme Court issued a decision in Roe v. Wade, a landmark decision that quickly became the most widely recognized case in the country. Examining the roots of ongoing struggles over reproduction in the United States, Mary Ziegler helps readers not only understand the importance of the Supreme Court⁰́₉s iconic decision in Roe but also places it in context, illuminating constitutional, political, and economic trends that have remade conflicts over abortion and the law. Written by one of the world⁰́₉s leading scholars in the field, this book synthesizes the latest scholarship in the field and provides an accessible and concise look at: *Why the United States criminalized abortion and birth control in the nineteenth century * Why there has been a stark disconnect between the law of the land and actual practice when it comes to controlling reproduction * What Roe v. Wade said and how the law and politics of abortion have moved beyond it With an up-to-date Guide to Further Reading, Who⁰́₉s Who of crucial figures, and a Glossary of key terms, this book provides a crucial introduction to students of women⁰́₉s history, American history and legal history.